ANALISIS TINGKAT KUNJUNGAN WISATAWAN KE KOTA BATU - Mahgfira Dwi Novian; Ida Nuraini (Program Studi Ekonomi Pembangunan, 2018)
Tourism is an important source of income for a country. The revenue is obtained from each tourist attraction in Batu City. The purpose of this study to describe and analyze the influence of tourism attractions, the number of restaurants and hotels towards the number of visitors in Kota Batu. The results show that the boundaries of tourism objects in the city of Batu consists of 4 parts: West, Eastern, Northern, Southern City of Batu. And the results of multiple linear regression analysis showed that the number of Object tourism, Number of Restaurant and Hotel have significant effect to Number of Visitors Tourism in Batu City. Variable number of tourism object has the biggest influence to the number of visitor in Batu City.Keywords: Tourism, Number of Visitors, Total Tourism Object, Number of Hotel and Restaurant.